2022
DOI: 10.3389/fpls.2021.798858
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Transcriptome Analysis Provides Candidate Genes for Resistance to Tomato Leaf Curl New Delhi Virus in Melon

Abstract: Tomato leaf curl New Delhi virus (ToLCNDV) emerged in the Mediterranean Basin in 2012 as the first DNA bipartite begomovirus (Geminiviridae family), causing severe yield and economic losses in cucurbit crops. A major resistance locus was identified in the wild melon accession WM-7 (Cucumis melo kachri group), but the mechanisms involved in the resistant response remained unknown. In this work, we used RNA-sequencing to identify disease-associated genes that are differentially expressed in the course of ToLCNDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 167 publications
0
4
1
Order By: Relevance
“…However, we did not detect differences in the expression levels of these R genes after artificial inoculation with ToLCNDV to resistant and susceptible melon germplasm reported in a previous study ( Fig. S12 , see online supplementary material) [ 63 ]. Furthermore, previous research indicated that the ToLCNDV transcription activator protein could be degraded through the autophagy pathway [ 52 ].…”
Section: Discussioncontrasting
confidence: 69%
“…However, we did not detect differences in the expression levels of these R genes after artificial inoculation with ToLCNDV to resistant and susceptible melon germplasm reported in a previous study ( Fig. S12 , see online supplementary material) [ 63 ]. Furthermore, previous research indicated that the ToLCNDV transcription activator protein could be degraded through the autophagy pathway [ 52 ].…”
Section: Discussioncontrasting
confidence: 69%
“…The ToLCNDV outbreak caused losses of over 20% of zucchini and melons in Spain and 80% of pumpkins in Italy ( Sáez et al., 2017 ; Panno et al., 2019 ; Crespo et al., 2020 ), whereas no significant losses of tomatoes have been reported in these regions due to this virus to date. Most studies have focused on different adaptations in susceptible or resistant/tolerant hosts to identify candidate genes against this virus using molecular techniques or high-throughput sequencing ( Kushwaha et al., 2015 ; Romero-Masegosa et al., 2021 ; Sáez et al., 2022 ). To date, no studies have been conducted to compare the biological characteristics and reveal the precise molecular mechanisms by which different ToLCNDV strains display distinct adaptations in the same hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Another SNP change was detected in MELO3C022339 (Glutaredoxin protein) with a moderate change in Trigonus (G/T) and a low change (C/T) in some Flexuosus, Ibericus 21AM, Trigonus, and WM7. This last change has already been linked to resistance DEGs (differential expressed genes) associated with the response to Tomato Leaf Curl New Delhi Virus (ToLCNDV), with the SNP being present in resistant WM7 but not in the susceptible Piel de Sapo variant Piñonet [33].…”
Section: Discussionmentioning
confidence: 99%